TEKNIK MULLIGAN PALING EFEKTIF DIBANDINGKAN MOBILISASI SEGMENTAL UNTUK PENINGKATAN KEMAMPUAN FUNGSIONAL PADA PEMBATIK TULIS DENGAN CERVICAL SYNDROME - Siti Nadhir Ollin Norlinta; RA Tuty Kuswardhani; M. Ali Imron; Ketut Tirtayasa; N. Adiputra; Muh. Irfan (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2019)
Background: Cervical Syndrome is pain resulting from the interaction of which often bump into between of muscles and ligaments well as the that deals with the posture, over activity of the degenerative from discus cervikalis and its ankle urination and pain the neck.Purpose: To know the provision of mulligan technique is better than it was a segmental mobilization of to improve the ability functional at batik wrote disorder cervical syndrome. This research is designed an experimental research randomized pre and post test two group design , in which the grouping of random based on this subject .A kind of design in this research measure pre test and post test treatment in ekperimen group 2 .1 group given manipulation techniques and the mulligan snags 2 given a segmental mobilization of manipulation.Results :of value the measurement of the ability functional cervical syndrome that measured by NDI before intervention in group mean ± SD 65.00± 7.90 and group 2 mean ± SD = 70.00 ± 7.50 with p= 0.188 (p>0.05) with means there was no significant difference in both grup. Then the result afterthe intervention with NDI a showed mean mean ± SD = 37.22 ± 13.01 in group 1 and mean ± SD = 56.11 ± 4.85 in group 2 abtained p= 0,005 (p<0,005) that indicates which means that initial value ndi group 1 and a group of 2 there is no difference meaningful .The results of value ndi after the intervention in the 1 and a group of 2 get value p = 0.005 ( p < 0.05 ) this indicates there is a difference in meaningful between the 1 and a group of 2 after conducted therapy exercise.Conclusion: the enhancement of value weighted ndi in group 1 ( engineering mulligan ) smaller than a segmental ) ( both in terms of a group of 2 .Thus , it can be said that engineering mulligan produce the reduction of pain is greater than a segmental mobilization of.